Analysis of the Sikola (Learning Management System) Service System in the Teaching-Learning Process at Universitas Hasanuddin - Haerul Haerul; Hasniati Hasniati; Muh Tang Abdullah (Enrichment : Journal of Management, 2022)
This study aims to determine the development of the use of technology related to the teaching and learning process, which is the interaction of the academic community between lecturers and students. The application services used are from lectures to end-of-semester exams. This application is expected to facilitate the teaching-learning process or an effective lecture and can be done remotely. Nevertheless, using this application is difficult and less effective for students and lecturers who complain that the access process is very convoluted. This study used a qualitative method with data collection techniques through interviews, where the academic community (lecturers and students) in each faculty at Hasanuddin University became research informants.